2013
DOI: 10.2478/ffp-2013-00014
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of flora in the undergrowth of park afforestations, rural plantings and oak-hornbeam forests

Abstract: The process of forest fragmentation has been observed in many countries, where plant species had adapt to different habitats, such as for example manor parks and rural plantings. A number of scientists have studied the parks as sites where waning environments and landscapes find their shelter. In 2011-2012, research was undertaken on diversity of vegetation in afforestations of parks, rural plantings and oak-hornbeam forests in Sandomierz Basin. In order to compare the means obtained univariate analysis of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Native forest plants typical for Tilio-Carpinetum community grow in shaded stands and on rich soils [55]. This was also observed by [57] and [58]. It is confirmed that the studied nature reserve in Tarnów has got more proper habitat conditions for forest plants compositions inside the forest than the ecotones and the inside of the urban forest studied by us.…”
Section: Resultssupporting
confidence: 78%
“…Native forest plants typical for Tilio-Carpinetum community grow in shaded stands and on rich soils [55]. This was also observed by [57] and [58]. It is confirmed that the studied nature reserve in Tarnów has got more proper habitat conditions for forest plants compositions inside the forest than the ecotones and the inside of the urban forest studied by us.…”
Section: Resultssupporting
confidence: 78%
“…According to Dzwonko (2015), these species are very sensitive to changes in habitat and occur only in natural or slightly transformed habitats. Similar research results were obtained by Fornal-Pieniak and Ollik (2013) and Fornal-Pieniak et al (2019). Some authors, including Palmer et al (2008) and Speziale and Ezcurra (2011), pointed to the fact that reduction of native flora enables the propagation of non-native species on the natural habitat.…”
Section: Discussionsupporting
confidence: 79%
“…Tilio-Carpinetum occupies the greatest area in the park. It is the most often documented community of non-maintained village parks (Fornal-Pieniak & Wysocki, 2006;Fornal-Pieniak & Ollik, 2013;Kucharski & Chmielecki, 2014. Ficario-Ulmetum (Kułak & Sender, 2011) and Fraxino-Alnetum (Borysiak et al, 2011a;Sobisz & Szmyt, 2015) are mentioned uncommonly.…”
Section: Discussionmentioning
confidence: 99%
“…The park was dissected by several gravel paths. Only remnants of the palace and a few-storey manor buildRegeneration of vegetation in manor park in Laskowice (Dąbrowa Forest District) Fornal-Pieniak & Ollik, 2013). Therefore the aim of the study herein is a characterization of plant communities for future revitalization of the park.…”
Section: Introductionmentioning
confidence: 99%